Does Improved Stereoacuity Lead to Retinal Structural Changes? - Shah, Mehul A.; Shah, Shreya M.; Alane, Narayan; Upadhyay, Pramod (Journal of Pediatric Neurology, 2016)
Aim To evaluate central macular thickness (CMT) following improved vision and stereoacuity in pediatric patients after medical intervention.Method We enrolled children having refractive errors, squint, or cataract. Anterior and posterior segment examinations were done with stereoacuity evaluated. We subjected all eyes for Spectral domain optical coherence tomography (SD-OCT) and measured CMT. After appropriate treatment, stereoacuity and OCT were evaluated again after 3 months.Result Here, we enrolled 229 children with mean age 10.6 ± 4.5 and found significant improvement in vision and stereoacuity after treatment (p < 0.05) in children with refractive errors, squint, and cataract.Conclusion Appropriate treatment makes functional changes in terms of stereoacuity as well as structural changes in form of CMT in children with refractive errors, squint, and cataract.
Keywords: central macular thickness; neuroanabolism; stereoacuity; titmus; vision development